Evaluation of Tribological Properties of Sulfur- and Phosphorous-Free Quinolinium Salts and Their Correlation with Quantum Chemical Parameters - Kalyani; Jaiswal V.; Rastogi R.B.; Kumar D.; Singh P. (My University, 2025)
For developing antiwear additives with high efficiency but with low sulfated ash, phosphorous, and sulfur (SAPS), N-substituted quinolinium halides, [DIP-Q]+Br−[DIP-Q=1-(3-(1,3-dioxoisoindolin-2-yl)propyl)quinolon-1-ium], [DIE-Q]+Br−[DIE-Q=1-(3-(1,3-dioxoisoindolin-2-yl)ethyl)quinolon-1-ium], [P-Q]+I−[P-Q=propylquinolon-1-ium], and [M-Q]+I−[M-Q=methylquinolon-1-ium] have been prepared and characterized by1H- and13C-NMR spectroscopic techniques. The tribological performance of these quinolone-based quaternary salts as antiwear additives in paraffin oil has been assessed on a four-ball test rig. The observed results have been compared with those of zinc dialkyldithiophosphate (ZDDP), a high SAPS additive. The tribotesting of these additives has been performed using 1% w/v additives concentration at different loads and times. The potential of these compounds as antiwear additives is evident from their observed tribological data: mean wear scar diameter (MWD), friction coefficient (µ), mean wear volume (MWV), and wear rates. All of the quinolinium derivatives prove to be better antiwear additives than ZDDP. Among the tested synthesized compounds, [DIP-Q]+Br−exhibits the best tribological behavior followed by [DIE-Q]+Br−, [P-Q]+I−, and [M-Q]+I−. The surface topography of worn surface studied by scanning electron microscopy (SEM) and atomic force microscopy (AFM) shows that surface roughness is reduced to a greater extent in case of quinolinium derivatives than lubrication with ZDDP or base oil alone. Energy-dispersive X-ray (EDX) and X-ray photoelectron spectroscopy (XPS) analysis of worn surfaces in the presence of quinolinium additives shows that the tribofilm is composed of FeBr3, Fe3O4, and organic compounds containing carbonyl and imine bonds. Theoretical investigations using quantum chemical calculations are indicative of significant chemical interactions of these quinolinium additives with metal surfaces, which is strongly supported by the observed experimental data. © 2017 Society of Tribologists and Lubrication Engineers.